Evaluating SOA formation from different sources of semi- and intermediate-volatility organic compounds from the Athabasca oil sands. Issue 3 (23rd March 2022) - Sommers, Jacob M.; Stroud, Craig A.; Adam, Max G.; O'Brien, Jason; Brook, Jeffrey R.; Hayden, Katherine; Lee, Alex K. Y.; Li, Kun; Liggio, John; Mihele, Cristian; Mittermeier, Richard L.; Stevens, Robin G.; et al.
Abstract : Organic aerosols are a major component of particulate matter but have a complex and uncertain effect on climate and health. Abstract : As an important component of particulate matter (PM), organic aerosols (OA) have a complex and uncertain effect on climate and health. The Athabasca oil sands in Canada are a significant source of secondary organic aerosol (SOA), despite low concentrations of combustion markers. Following recent intensive aircraft campaigns evaluating emissions and transformation of pollutants from the oil sands in 2013, multiple possible sources of primary semi- and intermediate-volatility organic compounds (P-S/IVOC) have been characterized, with divergent volatility distributions. This work uses a customized box model to evaluate four published volatility distributions against field measurements with respect to the corresponding evolution of OA concentrations as well as oxygen-to-carbon (O : C) ratios. Specifically, the volatility distributions evaluated are for oil sands ore and bitumen as well as for vapours from excavated oil sands deposits heated at 20 °C and 60 °C. The box model approach includes using an ensemble of several volatility basis set (VBS) parameterizations to model SOA. This approach allows exploration of parameterizations for SOA precursor oxidation and yields, molecular fragmentation, aging rate constants, and organic–organic phase separation. In contrast to urban regions, the model parameterizations which favoured more rapid formation of SOA typically led to biased-high OA concentrations at short photochemical ages. By comparing sensitivity studies for the SOA formation model, we were able to determine that the model is most sensitive to the parameterizations of primary IVOC oxidation, VOC oxidation and of multi-generational oxidative aging. Meanwhile, the sensitivities to the parameterizations for phase separation and fragmentation were weaker in the model. Within the ensemble of model parameterizations, the volatility distribution of vapours from excavated deposits heated to 60 °C performed the best among the four evaluated volatility distributions. This result suggests that the emissions of P-S/IVOCs are more strongly linked to the active mining and hot-water extraction of the oil sands. However, this work also highlights the need to quantify the specific sources of P-S/IVOCs within the oil sands operations, as the totality of SOA precursor emissions likely comes from a wide range of sources.